RE-EVALUATING THE MEANING AND EFFECT OF A WINDING UP ORDER ON THE INSOLVENT’S CONTRACTS Ellerine Brothers v McCarthy (245/13) [2014] ZASCA 46 (1 APRIL 2014) - Howard Chitimira (Obiter, 2018)
Notably, the Insolvency Act provides that a sequestration order is any provisional or final order of court that enables the insolvent’s estate to be sequestrated by the relevant creditors (s 2). In this regard, the article explores different interpretational challenges regarding the effect of a final sequestration order on the insolvent’s lease contracts (s 37 of the Insolvency Act) and the inconsistent application of section 348 of the Companies Act 1973 to such contracts as provided in Ellerine case (par 1−15). Related challenges involving the application of the provisions of the Companies Act 1973 to the winding up of insolvent companies have been unmasked in various South African cases to date.